Global, regional, and national burden of cutaneous malignant melanoma from 1990 to 2021 and prediction to 2045 - Liu, Chengling; Liu, Xingchen; Hu, Li; Li, Xin; Xin, Haiming; Zhu, Sailin (Frontiers in Oncology, 2024)
BackgroundCutaneous Malignant Melanoma (CMM) is a significant global health challenge. Understanding regional differences in CMM prevalence and trends is crucial for developing targeted strategies. To address this, we analyzed epidemiological patterns and investigated risk factors for CMM-related mortality.MethodsThis study analyzed CMM using data from the 2021 Global Burden of Diseases survey, covering 204 countries and territories. We evaluated the number and age-standardized rates of prevalence (ASPR), mortality (ASMR), disability-adjusted life years (ASDR), and annual percentage changes (EAPCs). Trends were stratified by region, country, age, sex, and Sociodemographic Index (SDI). A Bayesian Age-Period-Cohort model projected future prevalence, mortality, and DALYs, while decomposition analysis identified key drivers of CMM burden. Frontier analysis further associated CMM outcomes with socio-demographic development.ResultsIn 2021, the global prevalence of CMM reached 833,215 cases, a 161.3% increase since 1990. During this period, the ASPR rose from 19.13 to 25.37 per 100,000, while the ASMR declined from 0.84 to 0.73 per 100,000. DALYs increased by 60.5%, from 1,045,777 to 1,678,836. The high SDI region had the highest ASPR, ASMR, and ASDR. Decomposition analysis identified population growth, demographic aging, and epidemiological changes as equal drivers of CMM DALYs globally. Countries like New Zealand and Australia demonstrated the most significant effective differences, indicating potential for improvement in CMM management. By 2045, the global ASPR is projected to rise to 36.61, with ASMR and ASDR expected to decrease to 0.79 and 10.21 per 100,000.ConclusionCMM poses an increasing global health concern, with ASPR steadily rising. While this analysis shows a decline in global ASMR and ASDR overall, these rates are actually increasing in low SDI regions, and projections indicate that this trend will likely continue until 2045.